A structured exercise regimen enhances autonomic function compared to unstructured physical activities in geriatric horses - Kanokpan Sanigavatee; Chanoknun Poochipakorn; Onjira Huangsaksri; Sipaporn Vichitkraivin; Sireetorn Pakdeelikhit; Wanlapa Chotiyothin; Sirapatch Wongkosoljit; Thita Wonghanchao; Metha Chanda (Scientific Reports)
Abstract Older horses often show reduced autonomic responses, affecting their well-being. While regular exercise can help maintain autonomic function, the impact of structured exercise on geriatric horses is not well understood. A study involving 27 geriatric horses examined their autonomic modulation over 12 weeks under different activity levels. Horses were divided into three groups: (1) sedentary (SEL), (2) those participating in unstructured activities (RAT), and (3) those following a structured exercise regimen (SER). Results showed that the minimum and average heart rates decreased in the structured exercise group from weeks 10 to 12. In contrast, no changes were observed in the other groups. Furthermore, beat-to-beat intervals did not change in sedentary horses, fluctuated in horses engaged in unstructured activities from weeks 8 to 10 (p < 0.05), and increased in the structured exercise group during weeks 10 to 12 (p < 0.05). Heart rate variability was significantly higher in the structured exercise group compared to the unstructured group (p < 0.05–0.0001) and, to a lesser extent, compared to the sedentary group (p < 0.05). This suggests that structured exercise can lead to better autonomic regulation and lower stress in geriatric horses, highlighting the need for effective health management strategies post-retirement.